PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI INTERVENING VARIABLE PADA PERUM PERHUTANI UNIT 1 JAWA TENGAH - Hita, Yoti Gama; Pradhanawati, Ari; Hidayat, Wahyu (Jurnal Ilmu Administrasi Bisnis, 2013)
Abstraction Perhutani Unit I in Central Java is one of the State-owned enterprises (SOEs) that manage forest resources with the principles of sustainable forest management based on the characteristics of the region and Support Watersheds (DAS) as well as improving the results of forest wood and non-wood forest, ecotourism, environmental services, agroforestri as well as the potential for other forestry-based businesses in order to generate profits to ensure company growth in a sustainable way. The results of this research is that compensation demotivating work discipline, work on performance of employees in the Perhutani Unit I belonged to Central Java. The variable compensation gives the most powerful influence on the work achievement of work amounting to 50.5%. Variable work discipline gives influence of 45.0% of the employee's performance while 76.8% influenced by variables of motivation. The conclusion from this study is that compensation, work discipline and motivation of working effect significantly to employee performance intermediates.